An automation platform designs for electrical and electronics students: an application study - Bayrak, Gokay; Cebeci, Mehmet (Elsevier Science Bv, 2012)
Automation systems have been used in almost all areas of our lives so it is important for understanding and learning these systems for students, especially attend to technical schools. In this study, an application study was introduced for education of Electrical and Electronics students about programming, connecting and designing Programmable Logic Controller (PLC) and Supervisory Control and Data Acquisition (SCADA) systems and understanding automation systems. Thanks to designed automation platform, students can learn connections of PLC and SCADA systems, programming of these structures and they can improve and test new automation projects. (C) 2012 Published by Elsevier Ltd.
Cyprus International Conference on Educational Research (CY-ICER) -- FEB 08-11, 2012 -- Middle E Tech Univ No Cyprus Campus, CYPRUS
Keywords: PLC; SCADA; Automation System Education